Sistem Informasi Jasa Pindah Rumah Berbasis Website Dengan Metode Waterfall - Muhamad Fadly; Bambang Santoso (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of technology and software has advanced before it has involved the relationship between the needs of consumers and software developers. According to the South Tangerang City Central Statistics Agency, the city of South Tangerang, which is located in Banten province, in 2020 has a population of around 1,747,906.00, especially until 2022 the population of the city of South Tangerang, if we look at it with the naked eye, is getting denser. Thus the movement of population is certainly increasing, the occurrence of this displacement is sometimes a problem for those who are busy with daily work routines, Due to a busy work schedule plus less rest time, so that preparation for moving house to a new house or another rented house becomes difficult. it is difficult for them to do it as soon as possible, especially with the condition of the owner of the rented house asking them to immediately move from the rented house. The problems encountered as a result of this incident are starting from packing things, looking for a car to transport goods to tidying up the place to be occupied. tiring and time-consuming so that some have to take a day off from work to do it from the problems above, the author wants to make a website-based housewarming service application, this website application will provide various menu options ranging from the tools needed to perform services such as transporting goods, renting a car, to tidying things up in the new house that will be occupied.